AUTONOMY AND GOVERNANCE OF STATE UNIVERSITIES Case Studies in the University of Indonesia, the Jakarta State University, and the Syarif Hidayatullah State Islamic University - Soetjipto, Ani; Seda, Francisca Ery; Noor, Ida Ruwaid; Wardani, Sri Budi Eko; Soebagjo, Natalia (P2KK LIPI, 2014)
This paper explains the ways state universities construct the meaning as well as implementing the idea of autonomy and governance. Cases studies were conducted, which involved three Indonesian state universities, namely the University of Indonesia, the Syarif Hidayatullah Islamic State University, and the Jakarta State University. Through the Trakman’s model (2008) about the university governance, this paper underlines that there is no appropriate model to explain the autonomy and governance of Indonesian state universities. Result shows that the state’s role in the state universities is still dominant, both in the academic area, such as curriculum and dissemination of knowledge, and in the nonacademic area, such as finance; therefore, the autonomy seems to be taken for granted instead of being embedded. Moreover, there is ambivalence due to the state’s limited budget, which then allows the market and the global providing fund for higher education.